2013
DOI: 10.1002/fld.3858
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of lattice Boltzmann methods using bounce‐back schemes and immersed boundary ones for flow acoustic problems

Abstract: SUMMARYIn order to find applicable treatments of moving boundary conditions based on the lattice Boltzmann method in flow acoustic problems, three bounce‐back (BB) methods and four kinds of immersed boundary (IB) methods are compared. We focused on fluid–solid boundary conditions for flow acoustic problems especially the simulations of sound waves from moving boundaries. BB methods include link bounce‐back, interpolation bounce‐back and unified interpolation bounce‐back methods. Five IB methods are explicit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 48 publications
1
34
0
Order By: Relevance
“…1) can be diminished when the mesh size is D/100. [54]. The mesh spacing for the fluid is D/40, same as that used in Ref.…”
Section: Acoustic Waves Scattered By a Stationary Cylindermentioning
confidence: 99%
“…1) can be diminished when the mesh size is D/100. [54]. The mesh spacing for the fluid is D/40, same as that used in Ref.…”
Section: Acoustic Waves Scattered By a Stationary Cylindermentioning
confidence: 99%
“…As will become clearer later with the present work, although in certain cases the hydrodynamic force/torque evaluation does possess a second-order accuracy, such observation may not be generalized for arbitrary flows. Chen et al [19] compared a few IBB schemes and IBM-LBM algorithms in simulating the acoustic waves scattering on static and moving cylinder surfaces. They reported that while IBB schemes outperformed in accuracy in static cylinder cases, IBM-LBM could be a better choice in cases with moving objects in terms of suppressing the high-frequent fluctuations (i.e., the grid jitter problem) associated with objects crossing the grid mesh lines.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to overcome this problem is applying an inter-and extrapolation of the velocity at the boundary to determine a better approximation for the midpoint velocity [31]. Another approach to avoid the geometric discontinuity of the zigzag model is interpolation of distribution functions [30,38] at a node captured on the exact position of the particle boundary (Fig. 2b).…”
Section: Treatments Of a Moving Solid Boundarymentioning
confidence: 99%